BEHAVIORAL INTENTION TO USE E-WALLET DANA AS DIGITAL PAYMENT DURING THE COVID-19 PANDEMIC - Titahayu Ramadhanti Agus Sutjahjono; Muslimin (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine and examine empirically Perceived Easy of Use, Perceived Usefulness, Perceived Risk, and Service Feature against Behavioral Intention to Use E-Wallet DANA During The Covid-19 Pandemi. The object of this research is active users E-Wallet DANA in Indonesia with certain criteria. The Sampling technique using Slovin formula so that it can be obtained 100 respondents from total population of 50 million users.Data analysis in this study through the Partial Least Square (PLS) approach with the SmartPLS 2.0 M3. The Study’s result showed that Perceived Easy of Use, Perceived Usefulness, Service Feature has been proven to have a positive and significant effect on Behavioral Intention to Use E-Wallet DANA, and Perceived Risk has been proven positive and not significant effect on Behavioral Intention to Use E-Wallet DANA. Keywords : Perceived Easy of Use, Perceived Usefulness, Service Feature, Perceived Risk, Behavioral Intention to Use